Calix[4]resorcinarene-based hyper-structured molecular thermally activated delayed fluorescence yellow-green emitters for non-doped OLEDs. Issue 13 (4th March 2020) - Wang, Fanfan; Qiu, Weidong; Zeng, Jin; Yuan, Peng; Zong, Wansheng; Wu, Wenbo; Liu, Yingliang; Xu, Shengang; Su, Shi-Jian; Cao, Shaokui
Abstract : A series of novel hyper-structured molecular (HSM) thermally activated delayed fluorescent (TADF) emitters, in which the TADF units and host units are bound together into one inactive core through flexible linkages, were designed. Abstract : A series of novel hyper-structured molecular (HSM) thermally activated delayed fluorescent (TADF) emitters, in which the TADF units and host units are bound together into one inactive core through flexible linkages, were designed. Phenoxazine-triphenyltriazine (PXZ-Trz), 1, 3-bis(9 H -carbazol-9-yl)benzene (mCP) and calix[4]resorcinarene (CRA) were chosen as the TADF unit, the host unit and the core, respectively. A series of CRA-based HSM emitters, CRA-PXZ-Trz( X ) -mCP(100− X ) ( X = 0, 12.5, 25, 50, 75, 87.5 or 100) were successfully synthesized by a two-step click reaction. Upon using non-doped CRA-PXZ-Trz(87.5) -mCP(12.5) as the light-emitting layer, the solution-processable OLEDs emitted yellow-green light, and displayed an external quantum efficiency of 16.7% at 100 cd m −2 .